On the asymptotic of associate sigma-functions and Jacobi theta-functions - Korenkov, M. E.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
For the associated sigma-functions, Jacobi theta-functions, and their logarithmic derivatives, we present asymptotic formulas valid outside an efficiently constructed exceptional sets of discs.